Assessment of current prescribing practices using World Health Organization core drug use and complementary indicators in selected rural community pharmacies in Southern India. Issue 1 (December 2017) - Aravamuthan, Anandhasayanam; Arputhavanan, Mohanavalli; Subramaniam, Kannan; Udaya Chander J, Sam Johnson
Abstract Background Due to the lack of clear, comprehensive, and rational drug policy, the production of pharmaceutical preparations in India is distorted for the most part. Indian markets are flooded with more than 70, 000 formulations, compared to approximately 350 formulations listed in the World Health Organization (WHO) Essential Drug List. Studies have indicated that majority of prescriptions in India are of drugs of "doubtful efficacy." To promote rational drug use in developing countries, assessment of drug use patterns with the WHO drug use indicators is becoming increasingly necessary. The aim of this study was to assess the patterns of drug use by using WHO core drug use and complementary indicators. Methods One thousand fifty-two patients were prospectively interviewed and their prescriptions analyzed according to WHO guideline five randomly selected busy community pharmacies in northern district of the State of Tamil Nadu, South India to analyze the WHO core drug use and complementary indicators using an investigator-administered data collection form. The main outcome measured is patterns of drug use measured using WHO core drug use and complementary indicators. Results The data obtained showed that, out of total drugs prescribed (3936), only 2.5 % (100) drugs were prescribed by generic name. Mean number of drugs per encounter was 3.7. Use of antibiotics was 22 %, percentage of encounters with an injection was 7.2 %, and the percentage of drugs prescribed from formulary was 99.8 %. Conclusions Brand name prescribing is dominated even in rural India. There is a need to improve the availability of essential guidelines and key drugs in the stock in rural areas of India. Prescriptions studied were conforming to most indicators of WHO except the number of drugs prescribed & generic name prescription practice, which deviated. In India the healthcare is dominated by private practitioners at the primary level. Prescription practices of the individual community-based clinician needs consistent monitoring with respect to generic name prescribing habits as well as the number of drugs prescribed. The WHO drug use indicator guidelines need to be promoted amidst the primary care clinicians and should not be just limited to hospitals having a formulary. The data collected by this study can be used by policymakers to monitor and improve the prescribing and consumption of pharmaceutical products in Southern India.